MODIFICATION OF LIFESTYLE IMPROVES QUALITY OF LIFE AND ANTROPOMETRIC INDEXES IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASES IN COMBINING WITH OBESITY - Savchenko, L.; Kaidashev, I. (World of Medicine and Biology, 2017)
Aim - assess the effect of lifestyle changes on quality of life and anthropometric indicators in patients with COPD in conjunction with alimentary-constitutional form of obesity. тMaterials and methods. We examined 53 patients with COPD in combination with the alimentary-constitutional form of obesity, which were divided into two groups. Patients of the first group - the main, (n = 26) on the background of protocol therapy COPD was carried modification of lifestyle, which included training, nutrition correction and regular physical activity. Patients in the second group - (n = 27) received only protocol therapy for COPD. Patients’ examination included general clinical methods, determination of anthropometric indices (BMI, waist circumference (WC)), evaluation of COPD symptoms (CAT test) and quality of life (SGRQ). External respiration function was perform according to the generally accepted technique. The actual nutrition was evaluated using a 24-hour diet with food diary filling in two days - work and day off. Results and discussion. Prolonged use of lifestyle modification in the treatment patients with COPD in combination with obesity contributed to a decrease in WC of 1,07 times, BMI of 1,16 times (p